Crescimento e desenvolvimento de Physalis ixocarpa Brot. ex Hormen em diferentes condições de luminosidade - Silva, Natalina Souza (2016)
The tomatillo center of origin is in Mexico, being the fifth most produced vegetable in the country mainly used in the preparation of traditional Mexican cultural dishes. The principal means of spreading species from the genus Physalis are seeds. Physalis is considered easy to grow because of the quantity of seeds the genus produces, and its high rates of germination. This study aimed to characterize the developmental cycle and compare the growth of tomatillo 'purple' in two light conditions. For this purpose, P. ixocarpa 'purple' was grown in PVC pots with four replications of 10 samples for each treatment, a total of 40 plants per treatment. Evaluation of the seedling emergence was held in a range of 7, 14 and 21 days after sowing. The analysis of other phenophases started up to 26 days after sowing, was maintained throughout the cycle, and held in 14 days intervals. The estimated physiological parameters are the content of chlorophyll a and b, and leaf carotenoids. The plasticity of the species in the study was assessed using growth analysis with the variables height, stem diameter, number of leaves, buds, flowers and fruits, and dry weight of plant growth. Analysis was performed with the variables height, stem diameter, number of leaves, buds, flowers, fruits, dry mass of plants and leaf anatomy. The means of the data were assessed using analysis of variance (ANOVA) and the student T-Test with a 5% significance level. In this study the parameters that were influenced by light were the emergence rate of seedlings, the content of photosynthetic pigments, leaf thickness, period required for the establishment of phenophases, dry weight, fruit production and seed vigor. Although the plants grown in direct sunlight have higher rates of growth, greater production of fruits and viable seeds were obtained in plants grown under shade.